The Influence of KAP Size, Institutional Ownership, and Audit Committee on The Quality of Financial Statements - Kuncoro, Adris; Suryandari, Dhini (Universitas Pamulang, 2021)
This research aims to examine the relationship between KAP size, institutional ownership, and the audit committee on the quality of financial reports. 616 Indonesian Stock Exchange (IDX) companies in 2018 became the population in this study. Purposive sampling as a sampling technique resulted in 547companies. Using inferential logistic regression analysis and using descriptive statistical analysis hypothesis testing methods with IBM SPSS version 25 tools. This study found that the KAP size and the audit committee has a positive effect on the quality of financial reports. Institutional ownership does not affect the quality of financial reports. Simultaneously, KAP size, institutional ownership, and audit committee influence the quality of financial reports. This study concludes that partially, KAP size and audit committee has a positive effect on the quality of financial reports. Simultaneously, KAP size, institutional ownership, and audit committee affect the quality of financial reports. Further research suggests using other proxies, other periods, and other variables.